The effect of capital structure when expected agency costs are extreme - Harvey, Campbell R.; Lins, Karl V.; Roper, Andrew H. (Journal of Financial Economics, 2004)
This paper conducts powerful new tests of whether debt can mitigate the effects of agency and information problems. We focus on emerging market firms for which pyramid ownership structures create potentially extreme managerial agency costs. Our tests incorporate both traditional financial statement data and new data on global debt contracts. Our analysis is mindful of the potential endogeneity between debt, ownership structure, and value, and it takes into account differences in the debt capacity of a firm's assets in place and future growth opportunities. The results indicate that the incremental benefit of debt is concentrated in firms with high expected managerial agency costs that are also most likely to have overinvestment problems resulting from high levels of assets in place or limited future growth opportunities. Subsequent internationally syndicated term loans are particularly effective at creating value for these firms. Our results support the recontracting hypothesis that equity holders value compliance with monitored covenants, particularly when firms are likely to overinvest.